Vietnam : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper on Vietnam contains background material on banking sector reform, state enterprise reform, external trade liberalization, and tax reform. The paper highlights that banking sector reforms in Vietnam were focused on the creation of a two-tier banking system, the establishment of private sector banks, rationalization of the interest rate structure, and improvements in prudential and supervisory regulations. However, state commercial banks still dominate the banking system. Nonperforming loans are increasing, monetary policy continues to rely heavily on direct controls, and money markets remain rudimentary.